1999
DOI: 10.1136/fn.81.3.f184
|View full text |Cite
|
Sign up to set email alerts
|

Sodium potassium adenosine triphosphatase activity in preterm and term infants and its possible role in sodium homeostasis during maturation

Abstract: (Arch Dis Child Fetal Neonatal Ed 1999;81:F184-F187)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
11
1
1
Order By: Relevance
“…On the other hand, contrary to our present and the above mentioned previous findings,6 10-12 a recent study by Bistritzer et al 13 found that cord blood erythrocyte ATPase activity is lower in preterm neonates of between 30 and 34 weeks of gestation than neonates of ⩾ 35 weeks gestation. However, as Na + ,K + -ATPase activity has been reported to increase after birth in preterm neonates,8 it is possible that the use of cord blood by Bistritzer et al affected their findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, contrary to our present and the above mentioned previous findings,6 10-12 a recent study by Bistritzer et al 13 found that cord blood erythrocyte ATPase activity is lower in preterm neonates of between 30 and 34 weeks of gestation than neonates of ⩾ 35 weeks gestation. However, as Na + ,K + -ATPase activity has been reported to increase after birth in preterm neonates,8 it is possible that the use of cord blood by Bistritzer et al affected their findings.…”
Section: Discussioncontrasting
confidence: 99%
“…However, as Na + ,K + -ATPase activity has been reported to increase after birth in preterm neonates,8 it is possible that the use of cord blood by Bistritzer et al affected their findings. In support of this hypothesis is the fact that they themselves reported a postnatal increase in erythrocyte Na + ,K + -ATPase activity in their preterm neonates 13. Finally, our findings are strengthened by the enrollment of a larger patient population including more immature preterm neonates and by the downregulation of the α 1 subunit isoform in term neonates, suggesting the presence of an indirect relation between erythrocyte Na + ,K + -ATPase activity and gestational age.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Recently it has been reported that the expression and activity of Na + /K + -ATPase changes during perinatal and postnatal development [9][10][11]. The activity of the Na + /H + countertransport system also changes postnatally [12].…”
Section: Introductionmentioning
confidence: 99%
“…19 It may also play a role in sodium homeostasis during postnatal maturation in the premature infant. 20 Bradykinin is a major operative vasodilator that primarily affects pretubular renal arteries, contributing to an increase in GFR.…”
Section: Vasodilatorsmentioning
confidence: 99%